ANALISIS KINERJA BETON NORMAL DAN BETON DENGAN SEMEN SUBSTITUSI BLAST FURNACE SLAG - Tri Septa A.D., Qomariah, Akhmad Suryadi (Jurusan Teknik Sipil, Politeknik Negeri Malang, 2019)
The use of steel smelting waste industry is used to reduce the waste overflow at the site. The waste steel smelting industry called blast furnace slag (BFS) used as a substitution for cement in a concrete mixture in a Laboratory Material Test, Civil Engineering State Polytechnic of Malang. The purpose of this analysis is to: 1) Test the workability of normal concrete and concrete with BFS; 2) Find out compressive strength of each concrete; 3) Compare the price to both concrete in the construction of building.The required data were of gradation of aggregate, water content of aggregate, density of aggregate, absorption of aggregate, bulk density of aggregate, fineness of cement, normal consistency of cement, cement setting time, compressive strength of mortar cement, and the price of building materials Surabaya 2016. SNI 03-2834-2000 method was applied with variations BFS substitute of cement are 0%, 10%, 15%, 20%, and 30% BFS and the planned compressive strength obtained at 28 days of 300 kg/cm2.The analyses result in 1) The workability of each concrete: 5.75cm of normal concrete (0%), 3.45cm, 3.15cm, 3.1cm, and 3.05cm respectively with BFS concrete; 2) The compressive strength of each concrete at 28 days: 235.56kg/cm2 of normal concrete, 105.33kg/cm2, 138.96kg/cm2, 127.26kg/cm2, and 94.52kg/cm2respectively with BFS concrete; The use of BFS cannot be applied to the concrete mixture, because of low compressive strength; 3) For the price of concrete materials per m3 are IDR 999.472,05 of normal concrete, IDR 996.926,78 for 10% with BFS, IDR 995.654,93 for 15% with BFS, IDR 994.381,50 for 20% with BFS, and IDR 991.837,80 for 30% with BFS. Keywords: BFS, workability, compressive strength